Kinetics of CD4+ T Helper and CD8+ Effector T Cell Responses in Acute Dengue Patients - Manh, Dao Huy; Weiss, Lan Nguyen; Thuong, Nguyen Van; Mizukami, Shusaku; Dumre, Shyam Prakash; Luong, Quang Chan; Thanh, Le Chi; Thang, Cao Minh; Huu, Pham Thanh; Phuc, Le Hong; Nhung, Cao Thi Hong; Mai, Nguyen Thi; et al. (Frontiers in Immunology, 2020)
Background: The protective or pathogenic role of T lymphocytes during the acute phase of dengue virus (DENV) infection has not been fully understood despite its importance in immunity and vaccine development. Objectives: This study aimed to clarify the kinetics of T lymphocyte subsets during the clinical course of acute dengue patients. Study design: In this hospital-based cohort study, 59 eligible Vietnamese dengue patients were recruited and admitted. They were investigated and monitored for T cell subsets and a panel of clinical and laboratory parameters every day until discharged and at post-discharge from the hospital. Results: We described for the first time the kinetics of T cell response during the clinical course of DENV infection. Severe cases showed significantly lower levels of effector CD8+ T cells compared to mild cases at day −1 (p = 0.017) and day 0 (p = 0.033) of defervescence. After defervescence, these cell counts in severe cases increased rapidly to equalize with the levels of mild cases. Our results also showed a decline in total CD4+ T, Th1, Th1/17 cells during febrile phase of dengue patients compared to normal controls or convalescent phase. On the other hand, Th2 cells increased during DENV infection until convalescent phase. Cytokines such as interferon-γ, IL-12p70, IL-5, IL-23, IL-17A showed tendency to decrease on day 0 and 1 compared with convalescence and only IL-5 showed significance indicating the production during acute phase was not systemic. Conclusion: With a rigorous study design, we uncovered the kinetics of T cells in natural DENV infection. Decreased number of effector CD8+ T cells in the early phase of infection and subsequent increment after defervescence day probably associated with the T cell migration in DENV infection.